"With the Game on His Stick": The home (dis)advantage in National Hockey League shootouts - McEwan, D.; Martin Ginis, K. A.; Bray, S. R. (Psychology of Sport and Exercise, 2012)
Objectives: To determine whether a home advantage or disadvantage is evident in loss and win-imminent situations within National Hockey League (NHL) shootouts. Design: Archival. Method: Shooting percentages were analyzed from the 2006-2011 NHL seasons and shots were classified as: loss-imminent (when a miss results in a loss for the shooter's team); win-imminent (when a goal results in a win for the shooter's team); or non-outcome-imminent (when a miss or goal does not immediately determine the outcome of the game). Results: A home advantage was evident in loss-imminent situations when a team needed to score to avoid a loss. By contrast, a home disadvantage was evident in win-imminent situations when a team was shooting to win. Conclusion: The home (dis)advantage varies across different outcome-imminent situations. Comparing home and away teams' success in specific situations within a sporting match may be a valuable way of assessing the home (dis)advantage in sports.